Il Concetto di Numero nei Libri di Testo del Regno d’Italia: Indagini su un Particolare “Numero Complesso” (The Concept of Number in the Textbooks of the Kingdom of Italy: Investigations into a Particular “Complex Number”) - Silvia Cerasaro (Science & Philosophy)
Abstract From the arithmetic books of the schools of the Italian peninsula we can see complex numbers, different from imaginary ones. A complex number is a number accompanied by a unit of measurement, with submultiples not in decimal relation. After the introduction of the new system of weights and measures, the teaching of these numbers remains to help in the conversion. The procedures described by mathematicians who deal with complex numbers find their origin in a fraction described by Fibonacci in Liber Abbaci. It conveys a dynamic meaning of fraction on the number line, which has gradually fallen into disuse. This fraction, unlike complex numbers, was simple to interpret thanks to its symbolic formalism, which disappeared after the invention of printing, but was described in words in the books of subsequent centuries. Complex numbers were taught and learned in Italian schools until the ministerial programs of the 1923 Reform remained in force. Attention will be given to the historical context of the didactic uses of mathematical concepts, with the aim of arousing the epistemological reflections that usually derive from the use of history in mathematics education. Keywords: complex number, graduated multiple fraction